Eredia's description of Malaca, Meridional India, and Cathay - Godinho de Eredia, Manuel 1563- (MBRAS reprint, 1997)
This work by Malay Portuguese cartographer, Manuel Godinho de Eredia (1563-1623) retains its importance as one of the best early accounts of the Malay Peninsula, as well as its significance in the proto-history of Australian discovery. Besides maps depicting Melaka and the surrounding region "controlled" and "claimed" by the Portuguese around the city, it contains interesting information on the geneaology of the kings of Melaka up to 1511, the burial place of its founder Parameswara and on the traditional overland trails, the penarican (Malay penarican), the routes or short stretch that separates the Muar River and the nearest navigable tributary of the Pahang River that was once used by the local Malay population.